Tumor microenvironment-adjusted prognostic implications of the KRAS mutation subtype in patients with stage III colorectal cancer treated with adjuvant FOLFOX - Hye Eun Park (Nature Portfolio, 2021)
Abstract Several studies have reported that the prognostic effect of KRAS mutations on colorectal cancers (CRCs) varies depending on the type of mutation. Considering the effect of KRAS mutations on tumor microenvironment, we analyzed the prognostic significance of KRAS mutation types after adjusting for the tumor-infiltrating lymphocytes (TIL) and tumor-stromal percentage (TSP) statuses. In two independent cohorts, KRAS mutations were analyzed by Sanger sequencing and/or next-generation sequencing. TIL density and the TSP were quantified from whole-slide immunohistochemical images. KRAS-mutant CRCs were divided into three subgroups (G12D/V, other codon 12 mutations and codon 13 mutations) to examine their differential effect on TIL density, the TSP and recurrence-free survival (RFS). Among the KRAS mutations, only the G12D/V subgroups showed significantly less TIL infiltration than the wild-type CRCs. According to survival analysis, G12D/V mutations were associated with short RFS; codon 13 mutations showed discordant trends in the two cohorts, and other codon 12 mutations showed no significant association. Multivariate analysis further supported the prognostic value of G12D/V mutations. This result is not only consistent with a recent study suggesting the immunosuppressive effect of mutant KRAS but also provides insight into the type-specific prognostic effect of KRAS mutations.